User preferences related to multimedia elements of a mobile application to prevent diabetes (2020)
To understand user preferences related to the characteristics of an application that promotes and provides education on healthy habits to correctly design multimedia elements. Methods: We conducted a comprehensive qualitative study with a hermeneutical strategy, which gathered information using well-researched questions that were posed to focus groups consisting of 32 participants. These participants were asked for opinions related to multimedia elements to display educational messages about physical activity and healthy eating in a mobile application. There were three analysis categories of multimedia elements: text, visual elements, and audio elements. Results: The majority of the participants, 93.75%, were in the low socioeconomic stratum; 68.75% are in a civil union with their partner; 53.12% completed or failed to complete secondary school, and 68.75% were housewives. Based on the qualitative results, we found that mobile applications become mediating tools that support the adoption of actions that tend to improve lifestyles and increase knowledge about proper nutrition and physical activity. Text messages used in mobile applications should promote healthy habits and remind users of their benefits. Images and videos should be accompanied by text and audio to provide greater clarity regarding recommendations of healthy habits. Conclusions: Technology must provide accessibility and coverage opportunities, while meeting the needs and expectations of users. It should facilitate primary health intervention through education to transform unhealthy behaviors and generate lifestyles that improve the health of the user and their family context.